2020
DOI: 10.12688/f1000research.21599.1
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in metabolic and immune systems from pre-menopause to post-menopause: implications for age-associated neurodegenerative diseases

Abstract: The brain undergoes two aging programs: chronological and endocrinological. This is particularly evident in the female brain, which undergoes programs of aging associated with reproductive competency. Comprehensive understanding of the dynamic metabolic and neuroinflammatory aging process in the female brain can illuminate windows of opportunities to promote healthy brain aging. Bioenergetic crisis and chronic low-grade inflammation are hallmarks of brain aging and menopause and have been implicated as a unify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 200 publications
0
30
1
Order By: Relevance
“…Yet another key factor is timing and duration of estrogen use. Review of multiple prior animal studies suggested a critical window of time in which estrogen use may be beneficial for preserving brain structure and function (Daniel, 2013) (Wang, Mishra, & Brinton, 2020). We were unable to detect a significant effect of such an interval in our study.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Yet another key factor is timing and duration of estrogen use. Review of multiple prior animal studies suggested a critical window of time in which estrogen use may be beneficial for preserving brain structure and function (Daniel, 2013) (Wang, Mishra, & Brinton, 2020). We were unable to detect a significant effect of such an interval in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…In contrast, if too much time has elapsed from endogenous estrogen production and exogenous administration, no beneficial effect of estrogen on the brain was observed. Uncertainty remains about how these intervals translate to a human population and what genetic or environmental factors may modulate any such interval (Wang, Mishra, & Brinton, 2020). We were unable to detect a significant effect of such an interval in our study.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the US-American National Health and Nutrition Survey, women have a higher inflammation burden than men (the age range was 40–90+ years [ 15 ]). Especially postmenopausal women, like those included in the ESTHER study, have a high inflammatory burden because a decline in estrogen levels during menopause is associated with an increased expression of pro-inflammatory cytokines, including interleukin 6 and tumor necrosis factor (TNF) α [ 14 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially postmenopausal women, like those included in the ESTHER study, have a high inflammatory burden because a decline in estrogen level during menopause is associated with an increased expression of pro-inflammatory cytokines, incl. interleukin 6 and tumor necrosis factor (TNF) α (12,14,15). A cytokine storm as an adverse immune response to a SARS-CoV-2 infection is currently a major hypothesis for the underlying cause of a large proportion of COVID-19 deaths (16).…”
Section: Discussionmentioning
confidence: 99%